Analysis of the Prevalence of Ventricular Late Potentials in the Late Phase of Myocardial Infarction Based on the Site of Infarction - Benchimol-Barbosa,P. R. (2002)
OBJECTIVE: The initial site of myocardial infarction (MI) may influence the prevalence of ventricular late potentials (VLP), high-frequency signals, due to the time course of ventricular activation. The prevalence of VLP in a period of more than 2 years after acute MI was assessed focusing on the initially injured wall . METHODS: The prevalence of VLP in a late phase after MI (median of 924 days) in anterior/antero-septal and inferior/infero-dorsal wall lesion was analyzed using signal-averaged electrocardiogram in time domain. The diagnostic performance of the filters employed for analysis on was tested at high-pass cut-off frequencies of 25 Hz, 40 Hz and 80 Hz. RESULTS: The duration of the ventricular activation and its terminal portion were larger in inferior than anterior infarction, at high-pass cut-off frequencies of 40 Hz and 80 Hz. In patients with ventricular tachycardia, these differences were more remarked. The prevalence of ventricular late potentials was three times greater in inferior than anterior infarction. CONCLUSION: Late after myocardial infarction, the prevalence and the duration of ventricular late potentials are greater in lesions of inferior/infero-dorsal than anterior/antero-septal wall confirming their temporal process, reflecting their high-frequency content.